R E V I E W: Ecological distribution of Dipterocarpaceae species in Indonesia - PURWANINGSIH PURWANINGSIH (Society for Indonesian Biodiversity, 2004)
Dipterocarpaceae is one of the biggest family with >500 species in the world, and most of dipterocarps population aregrown in Indonesia which have high economical value of wood. One of the most important value from dipterocarps species is high on endemicities; there are up to 128 species (53.78%) from 238 dipterocarps species in Indonesia. Distribution of dipterocarps species would be affected by some factors especially edaphic, climate, and altitude. In Indonesia the dipterocarps species distribution could be shown from islands groups, number of species and forest types. Based on the observation of herbarium collection in Herbarium Bogoriense the distribution of the most dipterocarps species was in the altitude of 0-500 m and 500-1000 m on the dipterocarps forest type. Kalimantan and Sumatra were the two bigger islands with have the dipterocarps species distributed relatively high on population and species.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: Dipterocarpaceae, ecological distribution, altitude, Indonesia.